Perancangan Mesin Pencacah Serai Wangi Menggunakan Metode AHOQ Guna Meningkatkan Produktivitas Pascapanen - Wesly Mailander Siagian; Manaris Geraldo Silaban (Politeknik Pembangunan Pertanian Malang, 2024)
PT. Benimel Tani Bestari is located in Humbang Hasundutan and an experimental garden in Gurgur, North Sumatra, this agricultural business is developing the manufacture of medicines or more precisely the essential oil obtained from citronella (cymbopogon winterianus), the process of obtaining citronella essential oil through the extraction process, in To produce essential oils, the process carried out is to harvest citronella, then the withering process is carried out in order to reduce the water content in the material glands, he continued, the distillation process whose output from the distillation is essential oils, but in the business of PT. Benimel Tani Bestari, he did not carry out the counting process which by chopping can expand the evaporation area so that it is easier to extract, the advantage obtained by chopping is that it produces a higher percentage (%) of essential oil yields, this study aims to design a citronella chopper using the AHOQ (Axiomatic House of Quality) method, with Based on several steps, the design and specifications of the chopper are obtained, namely having wheels, pulling rollers, hooks to attach the chopping container, producing 2 cm - 4 cm chops, with the engine working system using a diesel-fueled dynamo.